2018
DOI: 10.4081/ejh.2018.2890
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of non-myelinating Schwann cells and their associations with leukocytes in mouse spleen revealed by immunofluorescence staining

Abstract: The nervous system and the immune system communicate extensively with each other in order to maintain homeostasis and to regulate the immune response. The peripheral nervous system (PNS) communicates specifically with the immune system according to local interactions, including the “hardwiring” of sympathetic/parasympathetic (efferent) and sensory nerves (afferent) to lymphoid tissue and organs. To reveal this type of bidirectional neuroimmune interaction at the microscopic level, we used immunofluorescent sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…In addition, in these reports, only scattered/sparse nerve fibers primarily associated with plexi along the trabeculae have been observed in the red pulp 13 . However, our study has demonstrated: (a) the presence of nerve fibers in each compartment of the spleen, including the splenic nodules, marginal zones, and red pulp, although the number of nerve fibers in the splenic nodules is much fewer compared with that of other compartments; (b) the intensity of nerve fibers in PALS and marginal zones is much higher than that of nerve fibers in some previous reports 11,[18][19][20] ; (c) the intensity of nerve fibers is similar to that of Remak fibers (indirectly demonstrated by non-myelinated Schwann cells) inside the spleen as shown in one of our previous studies 22 .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In addition, in these reports, only scattered/sparse nerve fibers primarily associated with plexi along the trabeculae have been observed in the red pulp 13 . However, our study has demonstrated: (a) the presence of nerve fibers in each compartment of the spleen, including the splenic nodules, marginal zones, and red pulp, although the number of nerve fibers in the splenic nodules is much fewer compared with that of other compartments; (b) the intensity of nerve fibers in PALS and marginal zones is much higher than that of nerve fibers in some previous reports 11,[18][19][20] ; (c) the intensity of nerve fibers is similar to that of Remak fibers (indirectly demonstrated by non-myelinated Schwann cells) inside the spleen as shown in one of our previous studies 22 .…”
Section: Discussionsupporting
confidence: 75%
“…Close associations/interactions of nerve fibers and DCs have been observed inside the spleen in some reports 24 . In our previous study, we have also detected close association of a few subsets of DCs with Remak fibers in the splenic white pulp and red pulp 22 . In the present study, we have revealed intensive nerve-DC associations.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations